Mental Health and Digital Practices of Family Caregivers in France Since the COVID-19 Pandemic - Lise Haddouk; Brian Tervil; Donovan Morel (Psychiatry International)
The COVID-19 pandemic and the related confinement it caused have led to significant social distancing. Family caregivers, an “invisible” population, seem to have been particularly affected by this context. In this sense, in this article, we question the psychopathological impact of this pandemic on caregivers, but also their use of digital tools and e-health as a lever. To do this, we applied a methodology involving both quantitative and qualitative data collection and analysis. We created and distributed an online survey and conducted interviews with the main caregivers of a person suffering from a physical, mental, and/or cognitive disorder, or an elderly person losing their independence. Our observations show that the psychological frailty of this population is important, with a fairly high prevalence of signs of anxiety (58.4%) and depression (50.7%), especially compared with the general population. In our sample, the use of digital tools did not seem to be in the context of e-health, but more in a social context of communication with others. This raises the following two important questions: Is it possible to predict and prevent the psychological frailty of caregivers? Can digital tools and networks of caregivers’ groups provide leverage and respite?